(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article shows the results of the use of the educational dialogue while studying foreign languages by senior pupils at comprehensive schools. The author gives some tables to demonstrate the effectiveness of the educational dialogue, which in the whole confirms the hypothesis of the research.